Kompetenzen im Bereich ‚Computational Thinking‘ von Schüler*innen in Deutschland im zweiten internationalen Vergleich - Eickelmann, Birgit; Vahrenhold, J.; Drossel, Kerstin; Niggemeier, Johannes Bernd; Niemann, Jan (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

TIMSS 2023: Wichtige Ergebnisse im Überblick - Schwippert, Knut; Kasper, Daniel; Eickelmann, Birgit; Goldhammer, Frank; Köller, Olaf; Selter, Christoph; Steffensky, Mirjam (TIMSS 2023. Mathematische und naturwissenschaftliche Kompetenzen von Grundschulkindern in Deutschland im internationalen Vergleich)

Die Perspektive der Lehrkräfte auf das Lehren mit digitalen Medien und die Förderung des Erwerbs computer- und informationsbezogener Kompetenzen in Deutschland im internationalen Vergleich - Drossel, Kerstin; Gerick, J.; Niemann, Jan; Eickelmann, Birgit; Domke, Marius (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

Die Perspektive der Schüler*innen auf das Lernen mit digitalen Medien und den Erwerb computer- und informationsbezogener Kompetenzen in Deutschland im internationalen Vergleich - Fröhlich, Nadine; Schaumburg, H.; Eickelmann, Birgit; Gerick, J.; Drossel, Kerstin; Domke, Marius (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

Die Perspektive der Schulleitungen auf digitalisierungsbezogene schulische Transformationsprozesse in Deutschland im internationalen Vergleich - Gerick, J.; Eickelmann, Birgit; Fröhlich, Nadine; Drossel, Kerstin; Niemann, Jan (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

Computer- und informationsbezogene Kompetenzen von Schüler*innen der 8. Jahrgangsstufe in Deutschland im dritten internationalen Vergleich - Eickelmann, Birgit; Bos, W.; Gerick, J.; Fröhlich, Nadine (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

Die IEA-Studie ICILS 2023 – Informationen zur Anlage und Durchführung der Studie - Eickelmann, Birgit; Fröhlich, Nadine; Bos, W.; Gerick, Julia; Goldhammer, F.; Schaumburg, H.; Schwippert, K.; Senkbeil, M.; Vahrenhold, J. (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

Technologische Rahmenbedingungen in Schulen in Deutschland im internationalen Vergleich - Niemann, Jan; Eickelmann, Birgit; Schaumburg, H.; Fröhlich, Nadine (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

ICILS 2023: Gesamtdiskussion der Ergebnisse und mögliche Entwicklungsperspektiven für Deutschland - Eickelmann, Birgit (ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich)

ICILS 2023 #Deutschland. Computer- und informationsbezogene Kompetenzen und Kompetenzen im Bereich Computational Thinking von Schüler*innen im internationalen Vergleich

ICILS 2023 im Überblick. Zentrale Ergebnisse, Entwicklungen über ein Jahrzehnt und mögliche Entwicklungsperspektiven - Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Fröhlich, Nadine

Portals across domains: A data analysis task and documentation canvas for data-driven model-based systems engineering - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman (System Innovation for an Artificial Intelligence Era)

Sustinnovate or perish: Principles for sustainable innovation - Wiederkehr, Ingrid; Tissen, Denis; Koldewey, Christian; Dumitrescu, Roman (System Innovation for an Artificial Intelligence Era)

Adherence to the Dietary Approaches to Stop Hypertension (DASH) diet is associated with lower visceral and hepatic lipid content in recent‐onset type 1 diabetes and type 2 diabetes - Schaefer, Edyta; Lang, Alexander; Kupriyanova, Yuliya; Bódis, Kálmán B.; Weber, Katharina S.; Buyken, Anette; Barbaresko, Janett; Kössler, Theresa; Kahl, Sabine; Zaharia, Oana‐Patricia; Szendroedi, Julia; Herder, Christian; et al. (Diabetes, Obesity and Metabolism)
Abstract Aim To investigate the associations of the Dietary Approaches to Stop Hypertension (DASH) score with subcutaneous (SAT) and visceral (VAT) adipose tissue volume and hepatic lipid content (HLC) in people with diabetes and to examine whether changes in the DASH diet were associated with changes in these outcomes. Methods In total, 335 participants with recent‐onset type 1 diabetes (T1D) and type 2 diabetes (T2D) from the German Diabetes Study were included in the cross‐sectional analysis, and 111 participants in the analysis of changes during the 5‐year follow‐up. Associations between the DASH score and VAT, SAT and HLC and their changes were investigated using multivariable linear regression models by diabetes type. The proportion mediated by changes in potential mediators was determined using mediation analysis. Results A higher baseline DASH score was associated with lower HLC, especially in people with T2D (per 5 points: −1.5% [−2.7%; −0.3%]). Over 5 years, a 5‐point increase in the DASH score was associated with decreased VAT in people with T2D (−514 [−800; −228] cm 3 ). Similar, but imprecise, associations were observed for VAT changes in people with T1D (−403 [−861; 55] cm 3 ) and for HLC in people with T2D (−1.3% [−2.8%; 0.3%]). Body mass index and waist circumference changes explained 8%‐48% of the associations between DASH and VAT changes in both groups. In people with T2D, adipose tissue insulin resistance index (Adipo‐IR) changes explained 47% of the association between DASH and HLC changes. Conclusions A shift to a DASH‐like diet was associated with favourable VAT and HLC changes, which were partly explained by changes in anthropometric measures and Adipo‐IR.

Correction: The acute effect of a β-glucan-enriched oat bread on gastric emptying, GLP-1 response, and postprandial glycaemia and insulinemia: a randomised crossover trial in healthy adults. - Revheim, I; Ballance, S; Standal, AF; Rieder, A; Dierkes, J; Buyken, Anette; Gilja, OH; Hausken, T; Rosendahl-Riise, H (Nutr Metab (Lond))

Determinants of Tax Complexity in Tax regulations and Tax Procedures - Evidence from a Developing Country - Schipp, Adrian; Siahaan, Fernando; Sureth-Sloane, Caren

Liquiditätseffekte einer Vermögensteuer bei Mietwohnimmobilien - Maiterth, Ralf; Piper, Yuri; Sureth-Sloane, Caren

Beschreibung des akustischen Verhaltens verklebter plattenförmiger Strukturen mittels Kopplungsmodellen - Zeipert, Henning; Hölscher, Jonas; Claes, Leander; Henning, Bernd (Fortschritte der Akustik - DAGA 2024)

Poisson structures in the Banach setting: comparison of different approaches - Tomasz Goliński, Tomasz; Rahangdale, Praful; Tumpach, Alice Barbora (Geometric Methods in Physics, XLI Workshop)

Herausforderungen beim Einsatz interaktiver Theorembeweiser in der Hochschullehre - Garnelo Abellanas, Irene; Liebendörfer, Michael (Beiträge zum Mathematikunterricht 2024)